In vitro Neo-Genesis of Tendon/Ligament-Like Tissue by Combination of Mohawk and a Three-Dimensional Cyclic Mechanical Stretch Culture System - Kataoka, Kensuke; Kurimoto, Ryota; Tsutsumi, Hiroki; Chiba, Tomoki; Kato, Tomomi; Shishido, Kana; Kato, Mariko; Ito, Yoshiaki; Cho, Yuichiro; Hoshi, Osamu; Mimata, Ayako; Sakamaki, Yuriko; et al. (Frontiers in Cell and Developmental Biology, 2020)
Tendons and ligaments are pivotal connective tissues that tightly connect muscle and bone. In this study, we developed a novel approach to generate tendon-like tissues with a hierarchical structure by introducing the tendon/ligament-specific transcription factor Mohawk (Mkx) into mesenchymal stem cell (MSC) line C3H10T1/2 cells and applying an improved three-dimensional (3D) cyclic mechanical stretch culture system. In our developed protocol, combination of stable Mkx expression and cyclic mechanical stretch synergistically affects the structural tendon-like tissue generation and tendon-related gene expression. In histological analysis of these tendon-like tissues, organized extracellular matrix (ECM) containing collagen type III and elastin was observed. Moreover, we confirmed that Mkx expression and cyclic mechanical stretch induced alignment of structural collagen fibril bundles that were deposited in a fibripositor-like manner during the generation of our tendon-like tissues. Our findings provide new insights for the tendon/ligament biomaterial fields.